Telehealth use for sexual and reproductive health promotion and care during the early phase of COVID-19 pandemic: A descriptive-interpretive qualitative study of healthcare providers' perspectives and experiences in Western-Central New York State. - Sadandaula Rose Muheriwa-Matemba; Danielle C Alcena-Stiner; Alexander Glazier; Natalie M LeBlanc (PLOS Global Public Health)
Telehealth emerged as a key option for the provision of sexual and reproductive health (SRH) care and promotion during COVID-19 pandemic restrictions. However, there is limited research on the perspectives and experiences of healthcare providers (HCPs) in the Western-Central region of New York State. This qualitative interpretive study explored the perspectives and experiences of the HCPs' with telehealth for SRH promotion and care including counselling, testing and treatment for HIV infection and other sexually transmitted infections (STIs), in Western New York State. Ten HCPs participated in semi-structured in-depth interviews conducted between October 2019 and February 2021. Participants were predominately White, female, with 1-30 years of clinical experience. The narratives revealed three major themes: 1) HCPs' perspectives of telehealth use, 2) HCPs' experiences with telehealth use for SRH promotion and care, and 3) determinants of telehealth implementation. Though all providers reported an increase in the use of telehealth, experiences in the delivery of telehealth varied especially for SRH services. Some providers reported having more time to consult with patients because patients could just call and schedule a telehealth visit and because of a decrease in patient load which freed up time to engage with patients. Others reported technological limitations among some patients which impacted care. Strengthening telehealth-based sexual health promotion will serve to address efforts toward ending the HIV epidemic, reducing other STIs, and ensuring consistent access to contraception. To effectively implement telehealth findings, suggest a need to ensure adequate technological resources for patients, and a need to increase HCPs' comfort to engage patients in sexual health conversations via telehealth.